2020
DOI: 10.1177/1071100720914856
|View full text |Cite
|
Sign up to set email alerts
|

Results After Percutaneous and Arthroscopically Assisted Osteosynthesis of Calcaneal Fractures

Abstract: Background: Operative treatment of calcaneal fractures using the extensile lateral approach is associated with high rates of soft tissue complications. In the past years, there has been a trend toward less invasive surgical approaches. Percutaneous and arthroscopically assisted calcaneal osteosynthesis (PACO) combines the advantages of visualization of the posterior facet of the subtalar joint with a minimally invasive approach. Methods: We conducted a follow-up of 25 patients with 26 calcaneal fractures (Sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…There is a notable lack of studies reporting the MOXFQ following calcaneal fracture surgery. Grün et al 15 reported a median MOXFQ Index score of 26.6 (0-76.6) following percutaneous and arthroscopically assisted calcaneal osteosynthesis that is greater than our study’s (28.6). Bremer et al 5 reported positive AOFAS scores (87 ± 13) at 24 months in their large series of displaced intraarticular calcaneal fractures that underwent operative fixation performed through a lateral subtalar approach.…”
Section: Discussioncontrasting
confidence: 86%
“…There is a notable lack of studies reporting the MOXFQ following calcaneal fracture surgery. Grün et al 15 reported a median MOXFQ Index score of 26.6 (0-76.6) following percutaneous and arthroscopically assisted calcaneal osteosynthesis that is greater than our study’s (28.6). Bremer et al 5 reported positive AOFAS scores (87 ± 13) at 24 months in their large series of displaced intraarticular calcaneal fractures that underwent operative fixation performed through a lateral subtalar approach.…”
Section: Discussioncontrasting
confidence: 86%
“…Previous studies have demonstrated that hollow screws have similar xation functions to the plates [17,18],Ni et al [19] described that adequate stability could be provided through the cross-screw technique,another study showed that longitudinal screw bear major stresses in standing position [20].Lv et al [21] described a double-point xation (DPF). Fixation of the posterior subtalar joint and calcaneal tuberculum can reduce the change in posterior articular surface displacement.Simon et al [22] achieved good results by xing DIACFs with a locking screw that xed the posterior subtalar joint and calcaneal tubercles.The above studies have demonstrated the reliability of DPF in xed subtalar joint and the good clinical results can be achieved, However, there are no systematic studies to guide the use of hollow screws,in order to provide better stability of the posterior articular surface and maintain the axial shape of the calcaneus, we recommend the use of hollow screw assisted plate xation in the case of severe calcaneal varus and posterior articular surface collapse.Protruding screws are an important reason for secondary surgery [23].In order to avoid screw irritation, the hollow screws should be embedded into the bone surface.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some scholars have proposed the use of arthroscopic targeting devices or preoperative prefabricated templates to improve the accuracy of screw placement into the sustentaculum tail, but the actual clinical situation is limited by many factors and di cult to promote. 8,15,19,30 Theoretically, the sustentaculum tail can be placed through any point on the lateral wall of the calcaneus but where is the exact point of placement of sustentaculum tail screws and the direction of screw placement still cannot reach consensus as it is useful for clinical guidance. 5,13,18,24 In this study, we reviewed and analyzed surgical treatment cases of calcaneal fractures in our hospital, all of which were treated with accurate placement of the sustentaculum tail screws, and de ned the cases in which the sustentaculum tail screws passed through the rst continuous bone trabecula on the lateral side of the central triangle of the calcaneus but not from the range of the sustentaculum tail as the sustentaculum fragment xation group, and compared the clinical e cacy of accurate xation of the sustentaculum tail with that of the displaced intra-articular calcaneal fracture, and speci ed the speci c location of the nail placement in order to guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%